THE TRANSLATION METHODS USED IN AN INDONESIA FOLKTALE ‘PUTRI LOPIAN’ - CHRONIKA ROSIANNA SIREGAR; Fauziah Khairani Lubis; Feriyanti Elina Gultom (LINGUISTICA, 2020)
This study was conducted by applying descriptive qualitative method. The source of data was taken from the folklore book and interviews with the translator of the folktale Putri Lopian. The technique for analyzing the data is descriptive qualitative research. The results of this research showed that there were 9% sentences by literal translation, 10 sentences by semantic translation, 5% sentences by adaptation translation, 31% sentences by free translation, 1% sentence by idiomatic translation and 10% sentences by communicative translation. The total number of sentences from the data consisted of 76% sentences. It was found there were seven out of eight types of translation methods Literal, Faithful, Semantic, Adaptation, Free, Idiomatic and Communicative uses based on the text in the Folktale. The reason why the translator used free translation as the dominant method was that he did not follow any theories or approaches of translation when he was translating the text; he thought that the audience was a child. so that he arranged the language to be easy to understand.  Keywords: folktale book; translation methods; text